UNIVERSITY EXTENSION AND POPULAR UNIVERSITIES: THE FREE EDUCATION MODEL AT THE UNIVERSIDAD POPULAR MEXICANA (1912-1920) - Torres Aguilar, Morelos (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The article results from a research on the university extension and the popular universities, seen as alternative models of education at the beginning of the XX century in Europe and America. The research focuses specifically on the Mexican Popular University (Universidad Popular Mexicana), whose educational model is intended to examine, reconstruct and compare with the others belonging to similar institutions of that time. It is to show that the application of the free model of education in those educational centers let the population, in general, have access to the higher education.